Calculations in hydraulic engineering : a practical text-book for the use of students, draughtsmen, and engineers : with numerous illustrations and examples. Part 1, - Fidler, T. Claxton 1841-1917 (Longmans' civil engineering series., 1898)
Rather than being a treatise on hydraulics, this book relates to the calculations which have to be made in connection with works of hydraulic engineering.